The Localized Lecture Video in Teaching Grade 11 Science Concepts (International Journal of Scientific Research and Management (IJSRM), 2022)
The study is focused on the development of localized lecture video that addresses the specific least learned competencies in Earth Science 11 in one of the big central schools in Surigao Del Sur, Mindanao, Philippines. The study employed developmental-evaluative design which equated to the development of the instructional material, the localized lecture video, based on the least learned competency in Earth Science 11. The tool utilized in evaluating the developed video was an adopted survey questionnaire from the Department of Education, Surigao Del Sur Philippines. The evaluation was done by expert-teachers and students after watching the uploaded video in the internet. Results show that teacher experts and students as evaluators rated the localized demo video very satisfactory in terms of integrity, learner’s focus, usability, accessibility, content, format/technical design, presentation/organization, accuracy and up-to-datedness of information. Findings revealed that the evaluation rating of teacher-experts has no significant difference to the evaluation rating of students. Moreover, the same results were attained in the evaluation rating of the teacher- experts and student on the localized demo video when it comes to audio and video recording, which shows no significant difference. According to experts, the generated localized demo film is a promising instructional material for use because it is suitable and respectable for learning reasons.